FAKTOR-FAKTOR PENYEBAB KEMUNCULAN PRASANGKA SOSIAL (SOCIAL PREJUDICE) PADA PELAJAR - Dede Rahmat Hidayat (Program Studi PPKn FIS UNJ & Asosiasi Profesi PPKn Indonesia, 2013)
This study aims to investigate of the factors in the emergence of social prejudice student groups. The subjects of this study were student grade junior high school VIII.1 232 Jakarta, consisting of 38 students. They are a group of people on a small scale that represents some ethnic elements. The sampling technique is done by using the technique of sampling convinience. Measuring tool used is a semantic differential scale is an instrument to measure the response of the aspects of affective. The results showed that social prejudices on the subject is at the level of medium and low. In addition, the student social prejudice caused more by prejudices that are more personal and social nature. The emergence of prejudice is caused by cultural differences and the social distance between different ethnic groups.